Spectral and Molecular Modifications of Hydrophilic Silica Aerogel: A Study on Doping Effects and Structural Evolution - Israa F. Al-sharuee; Orass Abdulhadi Hussein (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Silica gel has recently become an interesting material because of its importance in many applications in several fields such as medicine and sustainable technology. It has been found that the impregnation of some materials improves the synthetic properties of silica. Silica gel was prepared via mixed TEOS: ethanol: hydrochloric acid with molar ratios of 2:10:1.5. After doping with Diethyl in different concentrations 10-4, 10-5, and 10-6) g/cm3, the molecular properties were studied by examining the FTIR, and the UV spectrum of the prepared samples. The synthetic and morphological properties were investigated through BET and SEM and EDX. Results showed the ultra-violet to the visible (green) region at the concentration (10-5) g3, and doping was evident through the change in the absorption peaks for different concentrations. The FTIR spectrum remained unchanged, as well, the high specific surface area indicates the inner connection of the dye to the silica network, which makes it a promising material in improving the structural properties for industrial applications. Materials with a limited variety of homogeneous microporous materials except for some aggregation appear at a high concentration (10–4) g/cm3 due to diethyl particles.